Academic Senate Minutes 2002-12-19 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 11/14/02 and 12/5/02 deferred. Report from Senate Budget Committee. Resolution on Academic Planning amended. Resolution on Advising Issues tabled. First reading Lecturer's Resolution on Tenure Track Hires. First reading Resolution regarding Provost Search Committee Chair.